MicroRNA profiling in human diploid fibroblasts uncovers miR-519 role in replicative senescence - Marasa, Bernard S. (Impact Journals LLC, 2010)
MicroRNAs (miRNAs) are short non-coding RNAs that regulate diverse biological processes by controlling the pattern of expressed proteins. In mammalian cells, miRNAs partially complement their target sequences leading to mRNA degradation and/or decreased mRNA translation. Here, we have analyzed transcriptome-wide changes in miRNAs in senescent relative to early-passage WI-38 human diploid fibroblasts (HDFs). Among the miRNAs downregulated with senescence were members of the let-7 family, while upregulated miRNAs included miR-1204, miR-663 and miR-519. miR-519 was recently found to reduce tumor growth at least in part by lowering the abundance of the RNA-binding protein HuR. Overexpression of miR-519a in either WI-38 or human cervical carcinoma HeLa cells triggered senescence, as measured by monitoring β-galactosidase activity and other senescence markers. These data suggest that miR-519 can suppress tumor growth by triggering senescence and that miR-519 elicits these actions by repressing HuR expression.